2020
DOI: 10.3390/educsci10070186
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Benefits of a Standardized Patient Simulation in Pre-Placement Dietetic Students

Abstract: The purpose of this study was to evaluate the effect of a simulation-based learning (SBL) experience on perceived confidence in monitoring and evaluation, as part of the delivery of nutrition care of pre-placement dietetic students, and to describe their perceived value of the learning experience post-placement. A mixed method explanatory sequential study design was used. A confidence appraisal scale was developed and completed by students before (n = 37) and after (n = 33) a low fidelity simulation using a vo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 41 publications
1
1
0
Order By: Relevance
“…This was found in students both with and without prior healthcare experience. These improved outcomes are similar to several other studies among simulation experiences in dietetics [29,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…This was found in students both with and without prior healthcare experience. These improved outcomes are similar to several other studies among simulation experiences in dietetics [29,[32][33][34][35].…”
Section: Discussionsupporting
confidence: 90%
“…Students can improve their inquiry skills by inquiring with the SSP to avoid blind consultation after entering the clinic [10]. SSP can be used for students to practice face to face repeatedly, which can make students pay attention to clinical communication methods and skills and improve students' confidence [11], so that students will not feel embarrassed when they come into clinical contact with real patients. It doesn't make patients tired either.…”
Section: Inquirymentioning
confidence: 99%
“…The SBE literature is diverse in terms of primary outcomes, aims, methods, definitions, and discipline, making the literature difficult to interpret, despite being generally supportive of SBE [16,19]. Dietitian-led research on SBE appears to concentrate on assessment of student learning outcomes (e.g., knowledge uptake, students' perceived learning) and experience (e.g., satisfaction, lived experience), arguably offering a catalyst or invitation for mapping and knowledge synthesis [20][21][22]. For instance, dietetic educators in the United Kingdom found that interaction with simulated or standardized patients improved students' communication skills (e.g., attitudes towards learning, understanding importance of, and confidence in communication skills) [21].…”
Section: Introductionmentioning
confidence: 99%